Penanaman Nilai Toleransi Beragama oleh Guru PAI di SDN 015 Sawit Permai Kecamatan Dayun Kabupaten Siak Provinsi Riau - Saparius, Saparius; Aprison, Wedra (Indonesian Research Journal on Education, 2023)
The background of this research is that in the SDN 015 Sawit Permai school there are two religionsadhered to by the students at the school, namely Islam and Christianity which are joined in oneclass, but in SDN 015 the dominant number of students is Muslim. Even though they have different beliefs, basically in their friendship relationship they still tolerate each other without any label of having to be friends with fellow believers, Islam and Islam, Christianity and Christianity. At SDN 15, not only are the students of different religions, but the teachers there are also of different religions, the same is true of the students. Even so, there is no gap between Muslims and Christians, peace is still carried out in schools even though there are different religions. This type of research is a field research (field research) with a qualitative descriptive approach. Data collection techniques were taken through observation, interviews, documentation with key informants and supporting informants. Based on the results of the author's research, it can be concluded that the cultivation of the value of religious tolerance by PAI teachers at SDN 015 Sawit Permai, Dayun District, Siak Regency, Riau Province still exists but has not been maximally carried out, only limited to reminding and exemplifying and inculcating the value of religious tolerance by PAI teachers at SDN 015 Sawit Permai, Dayun District, Siak Regency, Riau Province, among others by respecting andappreciating interfaith, instilling tolerance in differences, maintaining mutual understanding,supervising, upholding mutual love.